2022
DOI: 10.1021/acs.analchem.2c01738
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient GSH-Responsive “Off–On” NIR-II Fluorescent Fenton Nanocatalyst for Multimodal Imaging-Guided Photothermal/Chemodynamic Synergistic Cancer Therapy

Abstract: Accurate diagnosis and effective treatment of malignant tumors under the interference of complex and diverse tumor microenvironments (TMEs) have become the focus of research. Herein, an innovative TME-activated biomimetic nanocatalyst with quad-modal imaging capabilities of second near-infrared (NIR-II) “turn-on” fluorescence imaging, magnetic resonance imaging (MRI), photoacoustic imaging (PAI), and photothermal imaging (PTI) was designed and developed for self-enhanced photothermal/chemodynamic synergistic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…With the rapid expansion of chemistry and materials science, nanotechnology shows great potential to overcome the limitations of conventional tumor therapy, and nanosystems (or nanotherapeutics) are regarded as one of the most promising strategies for better tumor treatment (Zhang P. et al, 2022). The recent reports have revealed that the combination therapy strategies with CDT nanosystems can optimize the therapy effects and minimize the toxicity and adverse effects of treatment (He et al, 2021;Yang et al, 2021;Liu Y. et al, 2022;Hao et al, 2022).…”
Section: Nanosystems For Cdt Based Combination Therapy Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…With the rapid expansion of chemistry and materials science, nanotechnology shows great potential to overcome the limitations of conventional tumor therapy, and nanosystems (or nanotherapeutics) are regarded as one of the most promising strategies for better tumor treatment (Zhang P. et al, 2022). The recent reports have revealed that the combination therapy strategies with CDT nanosystems can optimize the therapy effects and minimize the toxicity and adverse effects of treatment (He et al, 2021;Yang et al, 2021;Liu Y. et al, 2022;Hao et al, 2022).…”
Section: Nanosystems For Cdt Based Combination Therapy Strategiesmentioning
confidence: 99%
“…In addition, the imbalance of calcium transport channels caused by oxidative stress further promoted the calcification, inducing the necrosis of tumor cells (also named as ion interference therapy). Therefore, during ROS generation process, the Fenton-like reaction generated by Cu 2+ is synergistic with the mitochondrial dysfunction induced by Ca 2+ (Liu B. et al, 2022).…”
Section: Cdt-sonodynamic Combination Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve precise tumor visualization and localization, constructing multimodal imaging to exploit the advantages of various imaging techniques is considered an effective strategy. Recently, our group has reported a kind of water-soluble Ag 2 S quantum dots (QDs) with highly bright NIR-II fluorescence , and developed a multimodal imaging bioprobe with NIR-II “turn-on” fluorescence imaging, photothermal imaging (PTI), photoacoustic imaging (PAI), and MRI capabilities …”
Section: Introductionmentioning
confidence: 99%
“…At the same time, ROS are generated in organisms as metabolites or signaling molecules during cellular metabolism or in response to environmental stimuli . Furthermore, due to the unique oxidative properties of • OH, it has a wide range of applications in the degradation of environmental pollutants, cancer therapy, and analytical chemistry . Therefore, sensitive and accurate detection of • OH is also an important task in biosensing.…”
mentioning
confidence: 99%